Diseño de un sistema de energía solar fotovoltaica descentralizado para cubrir la demanda de energía eléctrica y hacer funcionar filtros para potabilizar agua en una vivienda tipo unifamiliar en el departamento del Chocó. (2022)
The purpose of this paper is to argue the proposal of a model of a photovoltaic solar energy system to cover the demand for electricity in a single-family house by means of simulated models using the pv-sol software tool. For delimitation purposes, the subregions into which the department of Choco is divided are proposed, due to the geographic and environmental conditions of this territory.